Potentials of Vernonica amygdalina Extracts as an Alternative Anti-Microbial Feed Additive in Poultry - Weniafere, Matilda E. (Indian Journal of Animal Nutrition, 2021)
Due to the problem of antibiotic resistance, the use of synthetic antibiotics has been restricted in animal farming, which has spurred research into the development of alternatives. This study was designed to assess the in vitro antibiotic activity of the water and ethanolic extract of bitter leaf against Salmonella sp, Shigella sp, Staphylococcus sp, Escherichia coli and Pseudomonas aeruginosa. Antimicrobial susceptibility test was done using Kirby-Bauer disc diffusion method. Results obtained showed that none of the organism tested was sensitive at 20% of the water extract. Sensitivity increased from 40% to 100% of the water extract. The highest zone of inhibition (ZOI) of 17.00±1.00 mm was obtained for Staphylococcus sp, followed by 16.33±1.15 mm for P. aeruginosa both at 100%. The highest ZOI for the ethanolic extract of bitter leaf (27.67±2.52 mm) was recorded for Staphylococcus sp followed by 25.00±2.00   mm for E. coli both at ethanol extract concentration of 300g /ml. We therefore conclude that bitter leaf can be considered as potential alternative to synthetic antibiotic growth promoters in poultry.